Wind field measurements over an forested escarpment by UAS during different seasons from 14 flights at the Swabian Alb - Kjell zum Berge; Andreas Platis; Jens Bange; Martin Schön (PANGAEA, 2022)
This dataset consists of meteorological measurements with a fixed wing UAS in the lower atmosphere above complex terrain in the Swabian Albs in south-west Germany. The UAS, equipped with fast sensors for all three wind components (u,v,w) and the air temperature as well as a slow sensors for humidity measured the wind field during 14 flights between the years 2018 ans 2021. The data was used to analyze the wind field and its modulation caused by a forested escarpment in perspective of a future installation of research wind energy turbines at that location. The data has been collected within the WINSENT ("Wind Science and Engineering in Complex Terrain") project, "https://www.windfors.de/de/projekte/testfeld/winsent/".